Indigenous girls and the violence of settler colonial policing - Dhillon, Jaskiran K. (Decolonization: Indigeneity, Education & Society, 2015)
In cities and towns across Canada, Indigenous girls are being hunted, harassed, and criminalized by local law enforcement agents and the Royal Canadian Mounted Police. These normalized outbreaks of state control, often punctuated by the use of deadly force, are not isolated incidents in an otherwise just and fair social order. Rather, they are reflective of Indigenous girls’ daily realities embedded within the structure of an ongoing settler colonial social context that has strategically invented the criminal justice system to secure and maintain settler sovereignty. As such, this paper aims to redirect our critical analysis of the policing and caging of Indigenous girls through the geopolitics of settler colonialism. In the wake of mass protests against colonial state violence throughout 2014, resistance decrying the justice system and insisting that #BlackLivesMatters and that Indigenous lives matter, I argue that we have an urgent need to listen to the stories that Indigenous girls have to tell. These are not just any stories, but narratives that profoundly destabilize the hubristic portrayal of Canada as a humanitarian nation cleansed of settler colonial rule.
Number: 2
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; cours; discipline; femmes* autochtones; femmes* et filles autochtones disparues et assassinées; féminisme décolonial; histoire et politique; pol4212; premier cycle; périodes historiques; régions géographiques; science politique; science politique et droit; système colonial; systèmes d'oppressions; thématiques; violence coloniale; violences; violences d'état

CIRFF 2015 - Conférence publique: «Race, colonialité & politique» avec Paola Bacchetta (2015)
Conférence de Paola Bacchetta, Université de Californie à Berkeley à la conférence publique «Race, colonialité et politique» organisée en collaboration avec l’Institut Simone-De Beauvoir au Congrès CIRFF2015, mercredi 26 août 2015, UQAM. 7e Congrès international des recherches féministes dans la francophonie (CIRFF2015) http://cirff2015.uqam.ca/ 24 au 28 août 2015, Université du Québec à Montréal.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; antiracisme; approches et analyses; asie; autochtones; décolonialisme; féminisme décolonial; genre; identités LGBTQIA2+; inde; politique; périodes historiques; queer; québec; ressource en ligne; régions géographiques; système colonial; systèmes d'oppressions; thématiques